PENGARUH ACETAMINOFEN TERHADAP AWITAN NYERI PASCA BEDAH ORTOPEDI ANGGOTA GERAK ATAS DI RS ORTOPEDI SURAKARTA - ALFIA, NURUL (2010)
Background: Surgery represent event having an effect on to body human being which have implication to pain in bone management. Pain in bone postoperative because of trauma, but other cause possibilities have to be considered. Better, prevention of pain in bone planned before operation to be patient is not annoyed by pain in bone after surgery. The analgesic betters are given before pain in bone arises with the adequate dose referred by pre-emptive. Medicines type and way of its gift base on the cause, pain in bone situation, and patient circumstance. Acetaminophen represent one of important drug for the medication of light pain in bone until is. Acetaminophen dose single effective for the therapy of pain in bone postoperative. Acetaminophens have the effect of anti inflammatory, analgesic and antipyretic. Purpose: To know the influence from acetaminophen in slowing down awitan of pain in bone postoperative of organ move for. That is by comparing onset of pain in bone postoperative for between patient gave the analgesic acetaminophen before operation (treatment group) with not given the analgesic acetaminophen (control group). Result: Pursuant to different test result of mean onset known that the mean onset for control group is 19,73 minute, whereas for the onset of treatment group is 69,33 minute. This matter indicate that the effective gift analgesic improve onset. Conclusion: Pursuant to research result of about influence of analgesic acetaminophen to pain awitan in bone postoperative patient of organ move for can be pulled conclusion: 1. Result of obtained by t statistical calculation value t count equal to 4,711 (p= 0,000 < 0,05); so that gift of analgesia acetaminophen have an effect on the significant to pain awitan in bone postoperative patient of organ move for. 2. Pursuant the data obtain can be taken conclusion that there is influence acetaminophen in slowing down pain awitan in bone postoperative patient of organ move for meaning its hypothesis proven.